The Development of A Corporate, Marketing, Operations, and Financial Strategy for A Swiss Cosmetics Start-up - Schmidt, Axel; Deshmukh, Swapnil (2010)
The aim of this Group Management Project is to explore the different strategies that can be implemented by a Switzerland based decorative cosmetics start-up business owned by one of the author of this document Mr. Axel Schmidt. The authors of this project Mr. Swapnil Deshmukh and Mr. Axel Schmidt are pursuing their MBA in Finance and MBA in Entrepreneurship degrees respectively and thus have provided insights gained from the overall MBA programme and particularly in their respective specialisations. The document consists of seven chapters elaborating on corporate, marketing, operations and financial strategies for the start-up business in decorative cosmetics. The Swiss decorative cosmetics industry is characterised by a fierce and turbulent market conditions dominated by multinational cosmetics firms. The first chapter introduces the authors and their reason and motivation behind this project, the concept of family start-up businesses, outsource production (private label) and the company lipCat Private Limited. The company lipCat Private Limited will indulge in selling decorative cosmetics products in the low price segment targeting young Swiss women on an online basis focussing only in Switzerland at its nascent stage. However, depending on the success of the business the company aspires to expand its operations to selected European countries. The second chapter reveals the corporate strategy of the company and includes the analysis of Swiss cosmetics market. Strategic tools such as SWOT, PEST and PORTER’S FIVE FORCES have been employed to gain more insight into the internal and external factors affecting lipCat. It also includes the analysis of its competitors, mentions the values, mission and the vision of the company owners. The chapter also mentions that lipCat will pursue a cost focus strategy based on its existing limited resources. The third chapter deals with the marketing strategy and defines marketing objectives of the company and underlining the different marketing mix options that lipCat plans to implements during its business operations. One of the major tools used in this chapter is consumer segment analysis, also different marketing steps such as creating an USP, Value proposition and copy strategy and brand personality. It also lays down the marketing budget and the marketing roadmap for lipCat. It also provides for certain marketing strategies that should be specifically implemented by start-up businesses. The fourth chapter exposes the operational activities of the business. It describes the process of the company starting with its purchasing the products from its supplier based in US to selling the products in the local Swiss market. The fifth chapter divulges the financial strategy of the company. It explore the existing financial structure of the company and how company can finance its future growth and expansion with its limited available resources. It also suggests for specific financial options that a small size business firm can explore to succeed. The chapter also includes and explore different strategic options that the company can explore in order to gain financial advantage. Finally it provides for different exit strategies in case of failure as well as success of the business. The sixth chapter mentions strategy implementation roadmap for lipCat based on the previous four strategy chapters. In the seventh chapter we conclude that lipCat as a business has certain negative aspects, such as reluctance of women to purchase decorative cosmetics over the internet and has limited resources to compete in the highly competitive market. However we also believe that the existence of a niche market, high flexibility and very low fixed costs will allow lipCat to exploit its potential in a manner that will yield positive results for the company.